Review on Caries Preventive Effect of Fluoride Toothpaste - Aldrin Joshua A1 , Keerthi Sasanka L2 , Gifrina Jayaraj3 , Dhanraj Ganapathy4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dental caries is defined as localized destruction of tooth tissue, mainly due to bacterial action causingdemineralized foci on peripheral surfaces. Normally, children have the habit of brushing their teeth once aday using fluoridated toothpaste. Due to this,there is less decay of tooth in them, as fluoride being a mineralprevents tooth decay. There is a relationship between fluoride toothpaste and dental caries, if a toothpastehaving 1000ppm of fluoride content, is associated with less decay of tooth, so the fluoride has cariespreventive effect. The aim of the review is to find out the role of fluoride in caries preventive effect, to knowfluoride toothpastes correct concentration to avoid fluorosis and other fluoride related ailments and finallyto understand the advantages of fluoride toothpaste as preventive effect of dental caries. This research wasconceived as scoping literature review. This review has accessed existing reviews and researches in the lastdecade mostly, through PMC database, MeSH, Google Scholar, Pubmed, Medline, CrossRef and the searchterms included were ‘dental caries’, ’fluoride toothpaste’, ’caries preventive effect’, ’fluoride’. Consideredresearch was limited to manuscripts related to English, dental caries, fluoride toothpaste (as caries preventiveeffect) and this review did not include or consider other oral problems, other preventive methods of dentalcaries, natural components that prevent caries attack. The description of included studies for the review istabulated. The role of fluoride in dental caries, its correct concentration in fluoride toothpaste is known andthe preventive effect of fluoride toothpaste on dental caries is well understood through this review. Withthese general guidelines, there is more possibility of preventing dental caries and excessive fluoride will notlead to fluorosis due to awareness of correct concentration of fluoride in fluoride toothpaste.